Hypoglycemia Impairs the Heat Shock Protein Response: A Risk for Heat Shock in Cattle? - Atkin, Samuel A.; Moin, Abu Saleh Md; Atkin, Stephen L.; Butler, Alexandra E. (Frontiers in Veterinary Science, 2022)
Background. Heat stress (HS) in cattle is a major debilitating problem, affecting health and milk yield. Physiologically, HS has been shown to lower blood glucose levels to 2.5mmol/l (45mg/dl) and results in upregulation of heat shock proteins (HSPs), eliciting the heat shock response (HSR) of which HSP90, 70 and 27 have been shown to be protective. However, it is unclear if the HSP response is blunted by decreased glucose, thereby preventing adaptive mechanisms. To address this question, this exploratory reverse translational study on the effects of hypoglycemia on the HSP pathway was undertaken. Methods. A human prospective, study in healthy control individuals (n=23) was undertaken. Subjects underwent hyperinsulinemic-induced hypoglycemia (≤2.0mmol/L(36mg/dl)) with blood sampling at baseline, at hypoglycemia and for a 24-hour post-hypoglycemia follow-up period. Proteomic analysis of the heat shock-related protein pathway, the pathway associated with HS in cattle, was performed. Results. In response to hypoglycemia, HS pathway proteins were significantly decreased (p<0.05): HSP70 and HSP27 (at hypoglycemia); DnaJ homolog subfamily B member 1 (DNAJB1), Stress-induced-phosphoprotein 1 (STIP1) and the ubiquitin pathway proteins, Ubiquitin-conjugating enzyme (UBE2L3) and Ubiquitin-conjugating enzyme E2 N (UBE2N) (at 30-min post-hypoglycemia); HSP90 (at 2-hours post-hypoglycemia). STIP1, UBE2L3 and UBE2N remained suppressed at 24-hours. Conclusion. Heat stress in cattle reduces blood glucose that, in turn, may blunt the HS pathway protective response, including HSP 90, 70, 27 and the ubiquitin proteins, leading to adverse outcomes. Monitoring of blood glucose in susceptible cattle may allow for earlier intervention and may also identify those animals at greatest risk to ensure that milk yield is not compromised.